E-user Verification Using Blockchain (JOURNAL OF SOFTWARE ENGINEERING TOOLS & TECHNOLOGY TRENDS, 2023)
The process of identification is quite hectic and recurring lots of fake identification are created for fraudulent transactions. It is a tedious work of carrying and managing all our documents. E-identity verification is the system which is proposed to make the process of identification easier and faster with one time user identification and then identifying the user based on the saved data. Recently, a new authentication protocol based on blockchain has been proposed to facilitate the sharing and management of IoT devices information in a distributed manner. It is claimed that this protocol ensures both user privacy preservation and security. However, a significant challenge arises due to the direct proportionality between data integrity and the associated costs of communication and computation. A central authority will store user data in a blockchain system, which can later be used to identify the user with their consent. Blockchain-enabled user identification reduces fraud user identification.